Pengaruh Citra Merek Terhadap Kepuasan Konsumen Pengguna Rokok Sampoerna Avolution Slim Menthol - Wattimena, Roy Alan (P3M Politeknik Negeri Ambon, 2023)
This research aims to analyze the influence of brand image on consumer satisfaction of Sampoerna Avolution Slim Menthol cigarettes. This research was conducted using a survey method of 100 respondents who were consumers of Sampoerna Avolution Slim Menthol cigarettes. Data were analyzed using simple linear regression analysis. The research results show that there is a positive and significant influence between brand image on consumer satisfaction with Sampoerna Avolution Slim Menthol cigarettes. This means that the more positive the brand image of Sampoerna Avolution Slim Menthol cigarettes, the higher consumer satisfaction with Sampoerna Avolution Slim Menthol cigarettes. Factors that shape the brand image of Sampoerna Avolution Slim Menthol cigarettes which influence consumer satisfaction include: product quality, price, promotion, brand personality and corporate social responsibility Keywords: brand image, consumer satisfaction